The role of governance in analysing waqf performance - Mohd Zeni, Nur Azni; Abdul Kadir, Mohd Rizuan; Sapuan, Noraina Mazuin (Springer, 2022)
Over the years, waqf institutions have played an essential role in addressing a wide range of socio-economic development for the ummah (society) all over the world. The growth of waqf with time has led to increasing expectations surrounding the role of waqf institutions. Nevertheless, there has been an inefficiency issue regarding waqf institutions in Malaysia. The literature em-phasises that inefficiency is usually associated with internal factors such as governance and management. Hence, the present study examines whether governance moderates the relationship between human capital in Waqf insti-tution and waqf regulations (both as a proxy of waqf management attribute) with waqf institutions' performance in Malaysia. The current research em-ployed a quantitative research methodology by analysing a selected sample of 99 respondents in waqf institutions. The developed model was tested us-ing the Structural Equation Model (SEM) technique through the Partial Least Square (PLS) approach. The results revealed a positive relationship be-tween waqf management attribute and waqf performance, which becomes stronger with high governance. Moreover, it should be noted that the use of governance as a moderator between waqf management attribute and waqf performance is very limited in past research. Therefore, the present study's result is expected to enhance the understanding of existing conceptual literature on the importance of governance in influencing the relationship be-tween waqf management attributes and waqf institutions' performance in Malaysia.